Internship Reports and Monography entitled: "The Pharmacist Role in High-Performance Sports: An Emerging Area" - Santos, Matilde Alves Pitadas (2023)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia